KONTRIBUSI DAYA LEDAK OTOT TUNGKAI DAN KELENTUKAN PERGELANGAN TANGANTERHADAP KEMAMPUAN LAY UP BOLA BASKET PADASISWA PUTRA SMP NEGERI 1 KELUMPANG - Sitti Maifa (STKIP Paris Barantai, 2019)
This research is a type of descriptive research. This study aims to determine: (1) To find out whether there is a contribution of leg muscle explosive power to the ability of basketball lay up results in male students of SMP Negeri 1 Kelumpang Hilir. (2) To find out whether there is a contribution of wrist flexibility to the basketball lay-up ability of male students of SMP Negeri 1 Kelumpang Hilir. (3) To find out whether there is a contribution to the power of the wrist flexing muscle to the basketball lay up ability of male students of SMP Negeri 1 Kelumpang Hilir. The population is male students of class VII and VIII of SMP Negeri 1 Kelumpang Hilir, totaling 179 people. The sample used was 40 male students of SMP Negeri 1 Kelumpang Hilir. The technique of determining the sample is by random selection by lottery (Simple Random Sampling). The data analysis technique used is descriptive analysis and inference analysis through the SPSS 24 program at a significance level of Î± 0.05. The results of the study indicate that; (1) there was a contribution of leg muscle explosive power to the ability of basketball lay up results in male students of SMP Negeri 1 Kelumpang Hilir, by 18.0%, (2) there was a contribution of wrist flexion to the ability to lay up basketball in male students of SMP Negeri 1 Kelumpang Hilir, by 18.1%, (3) there was a contribution of the explosive power of the muscles of the wrist to the basketball lay-up ability of male students of SMP Negeri 1 Kelumpang Hilir., By 19.6%. Keywords: Leg muscle explosive power, Wrist Flexibility, Lay Up